Effect of alternative ageing systems on the wine brandy sensory profile - Caldeira,Ilda (2013)
The wine brandies, as other alcoholic beverages, must be kept for several months (minimum of six months according to the European legislation) in wooden barrels, in order to achieve the minimum quality, before its consumption. However, the high costs related to ageing in wooden barrels have lead to the search of alternative technologies, such as the use of wood fragments, in order to accelerate the ageing process. In this work, the same wine brandy from Lourinhã was used to fill wooden barrels and stainless steel tanks with wood tablets or wood staves. These three ageing systems were studied with Limousin oak wood (Quercus robur L.) and Portuguese chestnut wood (Castanea sativa Mill.), with two replicates of each modality. The brandies were evaluated by sensory descriptive analysis during a period of 30 months. Colour, olfactory and gustatory attributes, previously generated by the tasting panel, were analysed. The results showed a significant effect of the ageing system on few sensory attributes. However, the most discriminant factors were the wood botanical species and the ageing time, which affected significantly several sensory attributes. Concerning the ageing system, the brandies aged in the presence of wood tablets presented lower intensity of the attribute golden and higher intensities of the attributes topaz, greenish, toasted, flavour, complexity and persistence in comparison with brandies aged in wooden barrels. The brandies aged in the presence of wood staves presented an intermediate sensory profile. Nevertheless, the overall quality of the brandies is not affected by the ageing system. These results pointed out the interesting sensory attributes of the brandies obtained with the alternative ageing systems; therefore further research is needed in order to validate the use of these technologies in the ageing of wine brandy.